Metabolic disease and ABHD6 alter the circulating bis(monoacylglycerol)phosphate profile in mice and humans - Grabner, Gernot F. (J Lipid Res, 2019)
Bis(monoacylglycerol)phosphate (BMP) is a phospholipid that is crucial for lipid degradation and sorting in acidic organelles. Genetic and drug-induced lysosomal storage disorders (LSDs) are associated with increased BMP concentrations in tissues and in the circulation. Data on BMP in disorders other than LSDs, however, are scarce, and key enzymes regulating BMP metabolism remain elusive. Here, we demonstrate that common metabolic disorders and the intracellular BMP hydrolase α/β-hydrolase domain-containing 6 (ABHD6) affect BMP metabolism in mice and humans. In mice, dietary lipid overload strongly affects BMP concentration and FA composition in the liver and plasma, similar to what has been observed in LSDs. Notably, distinct changes in the BMP FA profile enable a clear distinction between lipid overload and drug-induced LSDs. Global deletion of ABHD6 increases circulating BMP concentrations but does not cause LSDs. In humans, nonalcoholic fatty liver disease and liver cirrhosis affect the serum BMP FA composition and concentration. Furthermore, we identified a patient with a loss-of-function mutation in the ABHD6 gene, leading to an altered circulating BMP profile. In conclusion, our results suggest that common metabolic diseases and ABHD6 affect BMP metabolism in mice and humans.